Effect of reduction ratio on die fill-out and hardness profile of cold-drawn polygonal rods made of acid resistant steel X6CrNiTi18-10 - Rumiński, Maciej; Skubisz, Piotr; Micek, Piotr (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
The study investigates the effect of the reduction ratio on strain hardening efficiency and load during the drawing process of austenitic acid-resistant steel X6CrNiTi18-10. The focus is on optimizing geometry-related process conditions to achieve the highest quality and productivity when drawing special-purpose rods with polygonal shapes, specifically square and hexagonal cross-sections. The research addresses how increasing the reduction ratio can enhance strain hardening while reducing the number of drawing passes, ultimately affecting quality and load. Numerical modeling was used to analyze the relationship between strain hardening and load versus the reduction ratio. Proper models and assumptions were formulated and subsequently verified through experiments, which confirmed the validity of the mathematical and numerical models for load estimation. The study quantified the effect of strain on strength properties by mapping of measured hardness along the strain gradient. The application of variable billet diameters produced a similar hardness profiles for both analyzed rod geometries and reversed the effect on underfilling of the corners. The findings indicate a threshold reduction ratio for producing sound rods with square or hexagonal cross-sections. Exceeding this threshold can cause excessive strain hardening, leading to increased hardness that impedes corner fill-out and/or results in failure.